Pengajaran Digital Audio Workstation (DAW) Cubase kepada Sanggar Tari Runtiq Bulau - Vivian, Yofi Irvan; Arifin, M. Bahri; Wahyuni, Ian; Aprazaq, Fikri Yassaar (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
The progress of the times in the realm of art, makes traditional art increasingly eliminated. This is because traditional music has not been able to take advantage of technological developments, one of which is digital recording using the DAW Cubase 5. The purpose of this study is that the Runtiq Bulau Dance Studio will be able to document and record music digitally. This is one way to maintain the traditional arts of the Dayak Benuaq Tribe. The method used by the implementation team is descriptive research. The implementation team uses lectures, question and answer, and experimental methods. The lecture and question-and-answer methods are used by the implementation team to provide material. The experimental method is used by students to apply the material that has been given. Students can record music digitally using DAW Cubase 5. The instruments recorded were Kelentangan, two Gimars, and Gong recorded on four tracks. The recorded music is plate dance accompaniment music. In the mixing process, VST maximizer and reverb are used. This is done to maintain the authenticity of the sound from the instrument of tradition. VST Ozone 8 is used to simplify and speed up the mastering process. Now Runtiq Bulau Dance Studio can produce digital music independently.